Peran Semangat Kerja, Budaya Organisasi, dan Lingkungan Kerja Terhadap Kinerja PNS Kantor Desa Purwodadi - Daulay, Muhammad Toyib; Annisa Sanny; Putri Khairiyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
Spirit of work, organizational culture, and work environment influence the performance of civil servants. This research involved all civil servants of the Purwodadi village office, totaling 57 people. In this study, the technique of sampling by non-probability sampling is by using census sampling where the entire population is used as a research sample. This study used quantitative data processed with multiple linear regression models in SPSS 16. The results showed that morale, organizational culture, and work environment had a positive and significant effect on the performance of civil servants of the Purwodadi village office.